NK cells that differ in expression of NKp46 might play different roles in endometrium. (September 2021) - Mai, Chuxian; Fukui, Atsushi; Takeyama, Ryu; Yamamoto, Mayu; Saeki, Shinichiro; Yamaya, Ayano; Kato, Toru; Ukita, Yuji; Wakimoto, Yu; Shibahara, Hiroaki
Highlights: NKp46 plays different roles in reproduction based on its staining intensity. NKp46 dim NK cells are involved in cytotoxicity. NKp46 bright NK cells are involved in cytokine production. Direct modulation of NKp46 expression may help improve reproductive outcomes. Abstract: NKp46 is a natural cytotoxicity receptor expressed by NK cells and its expression is decreased in reproductive failure patients. NKp46 can be subdivided into NKp46 dim and NKp46 bright according to different fluorescence staining intensities. We investigated the role of the NKp46 receptor in determining the reproductive outcomes. Uterine endometrium was collected from 34 women with reproductive failure and divided into the pregnant and failed groups based on the results of a pregnancy reaction test during a 1-year follow-up period. NKp46 receptor and other activating or inhibitory receptors expressed on NK cells as well as intracellular cytokine production by NK cells were analyzed by multicolor flow cytometry. In the failed group, the percentage of NKp46 dim NK cells ( P < 0.05) was significantly higher and percentages of NKp46 bright NK cells ( P < 0.01) and CD16 − /CD56 bright NK cells ( P < 0.05) were significantly lower than those in the pregnant group. NKp46 dim NK cells were significantly and positively correlated with CD16 + /NKp46 dim NK cells; NKp46 bright NK cells were significantly and positively correlated with CD16 − /NKp46 bright NK cells. CD16 + /NKp46 dim NK cells were significantly and positively correlated with IFN-γ- and/or TNF-α-producing NK cells; CD16 − /NKp46 bright NK cells were significantly and positively correlated with TGF-β1-producing NK cells. We suggest that the NKp46 receptor plays different roles in reproduction based on the different fluorescence intensities associated with NK cells, i.e. NKp46 dim NK cells are involved in killing cells, whereas NKp46 bright NK cells are involved in cytokine production, indicating that NKp46 could be a predictive marker to see a tolerate condition for embryos.